2009
DOI: 10.1128/aac.01146-09
|View full text |Cite
|
Sign up to set email alerts
|

The Antituberculosis Drug Pyrazinamide Affects the Course of Cutaneous Leishmaniasis In Vivo and Increases Activation of Macrophages and Dendritic Cells

Abstract: Antileishmanial therapy is suboptimal due to toxicity, high cost, and development of resistance to available drugs. Pyrazinamide (PZA) is a constituent of short-course tuberculosis chemotherapy. We investigated the effect of PZA on Leishmania major promastigote and amastigote survival. Promastigotes were more sensitive to the drug than amastigotes, with concentrations at which 50% of parasites were inhibited (MIC 50 ) of 16.1 and 8.2 M, respectively (48 h posttreatment). Moreover, 90% of amastigotes were elimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 29 publications
5
35
0
Order By: Relevance
“…Despite the apparent dampening of acquired immunity, we observed significant increases in the levels of the TH1-associated cytokines IFN-␥, IL-12, and TNF-␣ using RT-PCR. A recent report demonstrated that PZA treatment of murine cutaneous leishmaniasis results in a 100-fold reduction in the parasite burden and increased macrophage activation and TH1 cytokine levels (34). It is apparent from the findings of our studies that the cessation of chemotherapy, including PZA therapy, resulted in a decline in TH1 immunity, supporting the findings of that recent study.…”
Section: Discussionsupporting
confidence: 82%
“…Despite the apparent dampening of acquired immunity, we observed significant increases in the levels of the TH1-associated cytokines IFN-␥, IL-12, and TNF-␣ using RT-PCR. A recent report demonstrated that PZA treatment of murine cutaneous leishmaniasis results in a 100-fold reduction in the parasite burden and increased macrophage activation and TH1 cytokine levels (34). It is apparent from the findings of our studies that the cessation of chemotherapy, including PZA therapy, resulted in a decline in TH1 immunity, supporting the findings of that recent study.…”
Section: Discussionsupporting
confidence: 82%
“…14 Many studies have shown that one or more of these drugs had a significant in vivo effect against Leishmania spp., 31,32 Plasmodium spp., 33,34 Toxoplasma gondii, 35 Wuchereria bancrofti, 36 Brugia malayi,…”
Section: Discussionmentioning
confidence: 99%
“…Further, PZA is the only antitubercular agent known to efficiently diffuse into the caseum of lung granulomas (16). PZA is also reported to modulate host immune responses (17,18). An immunomodulatory effect of PZA might be an additional factor contributing to TB treatment success.…”
Section: Introductionmentioning
confidence: 97%